Teaching motivation for student engagement - Meyer, Debra K.; Emery, Alyssa A. (Theory to practice : educational psychology for teachers and teaching, 2021)
"Helping teachers understand and apply theory and research is one of the most challenging tasks of teacher preparation and professional development. As they learn about motivation and engagement, teachers need conceptually rich, yet easy-to-use, frameworks. At the same time, teachers must understand that student engagement is not separate from development, instructional decision-making, classroom management, student relationships, and assessment. This volume on teaching teachers about motivation addresses these challenges. The authors share multiple approaches and frameworks to cut through the growing complexity and variety of motivational theories, and tie theory and research to real-world experiences that teachers are likely to encounter in their courses and classroom experiences. Additionally, each chapter is summarized with key "take away" practices. A shared perspective across all the chapters in this volume on teaching teachers about motivation is "walking the talk." In every chapter, readers will be provided with rich examples of how research on and principles of classroom motivation can be re-conceptualized through a variety of college teaching strategies. Teachers and future teachers learning about motivation need to experience explicit modeling, practice, and constructive feedback in their college courses and professional development in order to incorporate those into their own practice. In addition, a core assumption throughout this volume is the importance of understanding the situated nature of motivation, and avoiding a "one-size-fits" all approach in the classroom. Teachers need to fully interrogate their instructional practices not only in terms of motivational principles, but also for their cultural relevance, equity, and developmental appropriateness. Just like P-12 students, college students bring their histories as learners and beliefs about motivation to their formal study of motivation. That is why college instructors teaching motivation must begin by helping students evaluate their personal beliefs and experiences. Relatedly, college instructors need to know their students and model differentiating their interactions to support each of them. The authors in this volume have, collectively, decades of experience teaching at the college level and conducting research in motivation, and provide readers with a variety of strategies to help teachers and future teachers explore how motivation is supported and undermined. In each chapter in this volume, readers will learn how college instructors can demonstrate what effective, motivationally supportive classrooms look, sound, and feel like"--